Pengaruh Perhatian Orang Tua Terhadap Motivasi Siswa Belajar Pendidikan Agama Islam di SDN 03 Pakan Labuah - Adriani, Windi; Trisno , Bambang; Puadi , Asral (Indonesian Research Journal on Education, 2023)
This research is motivated by several problems that the authors found at SDN 03 Pakan Labuh, especially in the subject of Islamic Religious Education. Where in learning there are still some student scores that are under the Minimum Completeness Criteria (KKM) that have been determined. Various problems were raised including the lack of interest and motivation of students in participating in learning. Parentalattention is very necessary for a child to live his daily life. Attention from people who know willautomatically make the child's psychology better because children who still have an unstable soul usually need attention that can control their emotions so as not to do things that have a negative impact on them. Apart from that, the attention of parents will also automatically foster the enthusiasm of children to do anything, including learning. This study aims to describe the effect of parental attention on the motivationof students studying Islamic religious education at SDN 03 Pakan Labuh. This research is a qualitativeapproach research. Based on the results of the research that has been done, show that the forms of parental attention to the motivation of Islamic religious education students at SDN 03 Pakan Labuh include paying attention to giving warnings, giving reprimands, providing study facilities, setting children's study time, helping to solve problems and supervising learning by the parent. Thus, giving attention to children can increase their motivation to learn PAI. The obstacle faced by parents in paying attention to their children is the lack of time that parents have to gather with their children and the attitude of children that sometimes they become spoiled.